Semiautomatic dental recognition using a graph-based segmentation algorithm and teeth shapes features - Barboza, Elizabeth Bonsaglia [UNESP]; Marana, Aparecido Nilceu [UNESP]; Oliveira, Denise Tostes (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Dental recognition is very important for forensic human identification, mainly regarding the mass disasters, which have frequently happened due to tsunamis, airplanes crashes, etc. Algorithms for automatic, precise, and robust teeth segmentation from radiograph images are crucial for dental recognition. In this work we propose the use of a graph-based algorithm to extract the teeth contours from panoramic dental radiographs that are used as dental features. In order to assess our proposal, we have carried out experiments using a database of 1126 tooth images, obtained from 40 panoramic dental radiograph images from 20 individuals. The results of the graph-based algorithm was qualitatively assessed by a human expert who reported excellent scores. For dental recognition we propose the use of the teeth shapes as biometric features, by the means of BAS (Bean Angle Statistics) and Shape Context descriptors. The BAS descriptors showed, on the same database, a better performance (EER 14%) than the Shape Context (EER 20%). © 2012 IEEE.
Keywords: Biometric features; Dental radiographs; Descriptors; Graph-based; Graph-based segmentation; Human expert; Human identification; Radiograph images; Shape contexts; Teeth segmentation; Algorithms; Biometrics; Image segmentation; Graphic methods